2004
DOI: 10.1093/cep/byh033
|View full text |Cite
|
Sign up to set email alerts
|

Extramarital Affairs, Marital Satisfaction, and Divorce: Evidence from Hong Kong

Abstract: This article provides the first empirical study on how the perceived changes of marital satisfaction affect marital stability using a unique data set obtained in Hong Kong. It is found that the change of marital satisfaction due to extramarital affairs clearly increases the probability of divorce, but it is not the only determinant of marital instability. In particular, the presence of dependent children in a family and good marital quality before the discovery of extramarital affairs would lower the probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
1
11
0
2
Order By: Relevance
“…This does provide evidence for changing attitudes towards divorce. Nevertheless, the number of children a couple have still continues to be an important factor in predicting divorce in both South Korea (Lee, 2006) and Hong Kong (Fan and Lui, 2004). South Korea's dramatic rise in divorce rates has not surprisingly led to increased attention by researchers.…”
Section: South Korea Taiwan and Hong Kongmentioning
confidence: 99%
See 1 more Smart Citation
“…This does provide evidence for changing attitudes towards divorce. Nevertheless, the number of children a couple have still continues to be an important factor in predicting divorce in both South Korea (Lee, 2006) and Hong Kong (Fan and Lui, 2004). South Korea's dramatic rise in divorce rates has not surprisingly led to increased attention by researchers.…”
Section: South Korea Taiwan and Hong Kongmentioning
confidence: 99%
“…These normative changes could include erosion of any stigma attached to divorce and increasing acceptance of divorce as a way out of unhappy marriages. Women in the region now are less tolerant towards marital infidelity and seek divorce in such situations (Fan and Lui, 2004). In fact, in a survey of nearly 200 respondents who had knowledge about divorced women nearly three-fourths felt that the divorced women were happier after divorce (Chou, 2008).…”
Section: South Korea Taiwan and Hong Kongmentioning
confidence: 99%
“…This was an increase in the number of married men involved in extramarital affairs outside Hong Kong. According to research by Fan and Lui (2004), the presence of extramarital affairs is not the only determinant of marital instability, but it does tend to increase the probability of divorce.…”
Section: The Context and Development Of Family Mediation Services In mentioning
confidence: 99%
“…Indeed, dissatisfaction with sexual relationships can lead to serious problems in couples' relations resulting hatred of the spouse (Mulaviverdenjani , 2014). Fan & Lui (2004) reported a statistically dependant relationship between marital satisfaction and the quality of marital life. Based on a study on the United States Symond et al (2005) reported that sexual satisfaction was one of the most important factors in the quality of marital life in women.…”
Section: Abstract Introductionmentioning
confidence: 99%